(3GdEKHGJ HGdbQGFf aj GdehGO GdLfGFjI (B/ s - (3YWjI Ydj YWjI egfGs; (3eCehf eMeO SdGeI (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1988)
(3JHOC gPg GdQSGdI HaUd JegjOj Yf JGQjN GdEKHGJ HGdbQGFf hfXe GdEKHGJ, Ke jCJj GdHGH GdChd Yf CgejI GdbQGFf, hGdaUd GdKGfj Yf eGgjI GdbQjfI, hGdHGH GdKGdK Yf GdYedjGJ GdeJJGdjI ddEKHGJ HGdbQGFf, hCNjQG GdHGH GdQGHY Yf bjeI GdbQGFf aj GdEKHGJ, s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1988.s
(3jTJed Ydi EQMGYGJ HHdjhLQGaI UaMGJ (B265 - 282.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdEKHGJ HGdbQGFf s; (3fXe GdEKHGJs; (3CgejI GdbQGFfs; (3JYQja GdbQjfIs; (3JaSjQ GdbQGFfs; (3bejI GdbQGFf aj GdEKHGJs; (3GdbQGFf GdbGfhfjIs; (3GdbQGFf GdbVGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs